2001
DOI: 10.1038/sj.ejcn.1601141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of infant growth in the slums of Dhaka: size and maturity at birth, breastfeeding and morbidity

Abstract: Objective: To investigate the in¯uences of size at birth, breastfeeding and morbidity on growth during infancy in poor areas of urban Bangladesh. Design: This was a prospective observational study of a cohort of newborn infants followed until 12 months of age. Setting: Slum areas of Dhaka City in Bangladesh. Subjects: A total of 1654 newborn infants were enrolled at birth, and follow-up was completed for 1207 infants. Repeated anthropometric measurements and interviews of caretakers on infant feeding and morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
7
18
0
5
Order By: Relevance
“…Households with low economic status are less likely to access adequate food, health care, and quality education, and are also prone to preventable illnesses like diarrhea which result from an unhygienic environment; all of these factors serve to increase the risk of undernutrition. This study found a lower risk of underweight and wasting among children of middle compared to lower economic status households, as also supported by other studies [23,45]. …”
Section: Discussionsupporting
confidence: 90%
“…Households with low economic status are less likely to access adequate food, health care, and quality education, and are also prone to preventable illnesses like diarrhea which result from an unhygienic environment; all of these factors serve to increase the risk of undernutrition. This study found a lower risk of underweight and wasting among children of middle compared to lower economic status households, as also supported by other studies [23,45]. …”
Section: Discussionsupporting
confidence: 90%
“…Os resultados deste estudo indicam que as crianças cujas mães tinham estatura < 150 cm apresentaram estimativas negativas na média do índice comprimento/idade em escore Z, quando comparadas com aquelas crianças cujas mães tinham maior altura, corroborando achados de outros autores 20 . A altura materna tem se mostrado fortemente associada com o crescimento da criança, indicando possivelmente a influência da herança genética.…”
Section: Discussionunclassified
“…Thus a deficient environment is associated with current and ongoing exposure to nutritional deficiencies, resulting in inadequate gains in stature and body weight. Parental height has been shown to be negatively associated with a stunting among children (22,(37)(38)(39) . Results on maternal education and household wealth and child nutrition are congruent with those of other studies (10,22,40) .…”
Section: Discussionmentioning
confidence: 99%
“…Parental height has been shown to be negatively associated with a stunting among children (22,(37)(38)(39) . Results on maternal education and household wealth and child nutrition are congruent with those of other studies (10,22,40) . Maternal education and household wealth are associated with multiple positive factors including increased access to food and health-care resources (41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation